The fracture behaviors of the selective laser melting processed IN738 superalloy by in-situ tensile SEM - Morteza Taheri (Elsevier, 2021)
In this study, the ductility and fracturing behavior of IN738 superalloy, which was produced by selective laser melting, were investigated by the in-situ scanning electron microscopy (SEM) method at 700 °C. The results showed that the cavities nucleate mainly at the grain boundaries and inter-dendritic region (IDR). In these areas, sites with high-stress concentrations, including γ-γ 'eutectic and TiC carbide, are more prone to crack formation and propagation than other areas. With increasing strain to 27%, the IDR cracks propagated into the core-dendritic regions (CDR) and eventually caused the specimen to fracture. This was due to the presence of cavities that had formed in the CDR due to the outflow of moving dislocations from misorientation.